THE EFFECT OF SCIENTIFIC APPROACH OF PROBLEM BASED LEARNING (PBL) MODELS AND SOCIAL SKILLS ON STUDENT LEARNING OUTCOMES PPKN SUBJECTS CLASS V AT SDN 106161 LAUT DENDANG YEAR 2020/2021 - Ayu Listian Tarigan; Deny Setiawan; Daulat Saragi (SENSEI RESEARCH CENTER, 2021)
The purpose of this study is to determine: (1) To determine the effect of applying the scientific approach to the Problem Based Learning (PBL) model on student learning outcomes. (2) To determine the effect of Social Skills on student learning outcomes (3) To determine the interaction of the Scientific Approach Model Problem Based Learning (PBL) and social skills in influencing student learning outcomes of Civics. The population of this study was all fifth grade students at SDN 106161 Laut Dendang for the academic year 2020/2021. The sampling technique in this study was taken randomly using a lottery, determined 2 (two) classes as the experimental group, namely 1 (one) class being the Scientific Approach Treatment class and the 2nd class being the expository learning treatment class. The determination of the experimental class and the control class is the Problem Based Learning (PBL) model in the VA class30 Students and expository learning model in VB class 28 Students. The data analysis technique used was two-way ANOVA at a significance level of = 0.05, followed by the Scheffe test. The results obtained: (1) the average PPKn learning outcomes of students with Problem Based Learning (PBL) learning is 24.37 higher than students with expository learning of 19.46. (2) the average civics learning outcomes among students who have high social skills get an average score = 24.15, while the civics learning outcomes of students who have low social skills get an average score = 20.25 (3) there is no interaction between the use of the learning model and students social skills (high and low), namely the high social skills group (26.69), and the low social skills group (22.59), which is greater than the students who are taught with expository learning, namely the high social skills group (21.62), and the low social skills group (17.60). The results of data analysis concluded that students with high social skill characteristics used the Problem Based Learning (PBL) learning model and obtained a high average. While low social skills using the Expository model will get a low average. The implication of this research is that efforts to improve the teaching and learning process provide a more meaningful learning experience for students, one of the efforts that teachers can do is through the use of Problem Based Learning (PBL).